2019
DOI: 10.1002/2211-5463.12746
|View full text |Cite|
|
Sign up to set email alerts
|

TSLP induces a proinflammatory phenotype in circulating innate cells and predicts prognosis in sepsis patients

Abstract: Thymic stromal lymphopoietin (TSLP) has been identified as a crucial inflammatory cytokine in immune homeostasis. Previous studies have reported conflicting effects of TSLP on sepsis in mice, and the effect of TSLP on sepsis in humans has not been investigated. In this study, we used the ELISA to measure serum levels of TSLP in patients with sepsis, and used flow cytometry and ELISA to evaluate the proinflammatory phenotype of circulating immune cells. In addition, we used quantitative RT‐PCR to examine the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Overall, they conclude that the upregulation of TSLP in sepsis aims to restore immune hemostasis by dampening inflammation (44). In contrast, Yu et al demonstrated a negative correlation between serum TSLP levels in patients with high ratio of neutrophils and increased mortality in a septic patient cohort (47). Moreover, they showed TSLP induces inflammation in neutrophils and T lymphocytes and certain monocyte subtypes (intermediate and non-classical) leading to increased production of e.g.…”
Section: Dynamics In Trauma and Sepsismentioning
confidence: 96%
See 4 more Smart Citations
“…Overall, they conclude that the upregulation of TSLP in sepsis aims to restore immune hemostasis by dampening inflammation (44). In contrast, Yu et al demonstrated a negative correlation between serum TSLP levels in patients with high ratio of neutrophils and increased mortality in a septic patient cohort (47). Moreover, they showed TSLP induces inflammation in neutrophils and T lymphocytes and certain monocyte subtypes (intermediate and non-classical) leading to increased production of e.g.…”
Section: Dynamics In Trauma and Sepsismentioning
confidence: 96%
“…In trauma and sepsis, IL-10 is considered a key immunosuppressive cytokine and correlates with injury severity and outcomes (45) and is widely examined in sepsis and trauma studies. However, it has been demonstrated that all three cytokines also exert pro-inflammatory functions under certain conditions (46)(47)(48). This seems contradictory as they are considered key regulators of immunity.…”
Section: Mediators Of Immunosuppressionmentioning
confidence: 99%
See 3 more Smart Citations